Level of Gastrin Serum and Ulcer Size on Gastric Ulcer Correlated to Helicobacter pylori Infection - Dasril Efendi; Rustam Effendi; Leonardo Basa Dairy; Juwita Sembiring; Betthin Marpaung; Mabel Sihombing; Sri Maryuni Soetadi; Lukman Hakim Zain (The Indonesian Society for Digestive Endoscopy, 2009)
Background: Previously has been defined that peptic ulcer has strongly correlated to Helicobacter pylori (H. pylori) infection. But it hasn’t determined about correlation of gastrin serum level to the ulcer severity on H. pylori infection. The aims of this study were to find the percentage of H. pylori infection on peptic ulcer cases and its correlation to the gastrin serum level. Method: This is analytic cross sectional study in 50 patients with gastric ulcer who came to Adam Malik hospital from February to October 2007. The correlation between gastrin serum level and the size of ulcer with positive and negative Urea Breath Test (UBT) group was analyzed by unpaired student t- test. The correlation between gastrin serum level and ulcer size were investigated with Pearson correlation test and linier regression. Result: Fifty eligible patients, 33 (66%) had positive UBT and 17 (34%) were negative. There were statistically significant difference on gastrin serum level in positive UBT and negative respectively (p = 0.017). There were also significant difference between mean of ulcer size in positive UBT and negative respectively (p = 0.025). There were correlation between gastrin serum level and ulcer size (r = 0.315; p = 0.026). It can predict the increasing ulcer size in 0.012 mm every 1 pg/mL of gastrin serum elevated. Conclusion: Patients with positive UBT has greater ulcer size and higher gastrin level as compared to the negative group. There were positive correlation between gastrin serum level to the size of ulcer in peptic ulcer patients and increase of ulcer size followed with elevated of gastrin serum level. Keywords: Helicobacter pylori infection, gastrin serum level, ulcer size